A REVIEW ON PREVENTIVE MEASURES IN HYPERTENSIVE CHILDREN - Kumar Singhal, Harish (International Journal of Ayurveda and Pharma Research, 2015)
Considerable advances have been made in detection, evaluation, and management of high blood pressure, or hypertension, in children and adolescents. Because of the development of a large national database on normative blood pressure (BP) levels throughout childhood, the ability to identify children who have abnormally elevated BP has improved. Still perusal to Ayurvedic texts provides no straight reference to hypertension but on tunneling down the texts and arranging the scattered references from different texts, this is evident that Hridya and process of Rasa Vikshepa or Anudhavana by Vyana vayu has become helpful to understand the hypertension. Based on developing evidence, it is now apparent that primary hypertension is detectable in the young and occurs commonly. The long-term health risks for hypertensive children and adolescents can be substantial; therefore, it is important that preventive measures be taken to reduce these risks and optimize health outcomes, which are discussed in this paper.